Problems Faced by Automobile Industries: Case Study on Tesla - Bhardwaj, Shelly; Pandey, Rudresh; Sharma, Shobha; Sejal, Shivani; Iyer, Ganesh; Sharma, Shivam; P.V, Ranjith; Kulkarni, Swati (International Journal of Tourism and Hospitality in Asia Pasific, 2020)
The study is being done on the problems faced by Automobile Industries while launching Electric Cars. The problems are common for all the automobile industries which had launched the EV, are launching or will launch them. But here the research is done specifically in respect to Tesla. Tesla Motors Inc. is an American automotive and energy company that was founded in 2003 is based in Palo Alto, California. The company specializes in electric car manufacturing, SolarCity subsidiary and solar panel manufacturing. The company is well known for its exclusive models like Model S, Model 3, Model X and the newest one Model Y. Tesla Motors released its first electric car in 2008 that was called The Roadster. Roadster achieved 245 miles (394 km) on a single charge. Since 2008, Tesla sold approximately 2,450 Roadster in over 30 countries through December 2012. Tesla faced many problems while launching the very first EV not only with the model but with its marketing too. So, this Project Report is being prepared by researching the problems faced by the Tesla regarding its first EV and its marketing. There are some particular solutions that are recognized by our team for the respective problems which will be useful for the automobile industries to overcome certain problems. These solutions will open the doors for the industries that are going to launch EV by referring the past data analysis of Tesla which is studied and prepared by our team in this Research Project.